2021
DOI: 10.3390/agriculture11090836
|View full text |Cite
|
Sign up to set email alerts
|

Context Specificity and Time Dependency in Classifying Sub-Saharan Africa Dairy Cattle Farmers for Targeted Extension Farm Advice: The Case of Uganda

Abstract: Despite the huge potential for milk production, interventions to improve productivity in sub-Saharan Africa (SSA) are barely based on specified farm classifications. This study aimed to develop robust and context-specific farm typologies to guide content of extension farm advice/services in Uganda. From a sample of 482 dairy farmers, we collected data on farmer socio-demographics, farm management practices, ownership of farm tools and facilities, willingness to pay for extension services, milk production, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 92 publications
(116 reference statements)
0
3
0
Order By: Relevance
“…Agricultural extension and advising services are critical agents in agricultural development, poverty alleviation, and food security [ 29 ]. Agricultural extension and advisory services can help farmers address production and management issues by improving their technical knowledge, farm management skills, and information systems, resulting in increased production, higher economic returns, and a boost to the national and global economies [ 29 ]. Extension services and delivery techniques, on the other hand, are often unsuccessful in meeting the needs and technological hurdles that farmers face [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Agricultural extension and advising services are critical agents in agricultural development, poverty alleviation, and food security [ 29 ]. Agricultural extension and advisory services can help farmers address production and management issues by improving their technical knowledge, farm management skills, and information systems, resulting in increased production, higher economic returns, and a boost to the national and global economies [ 29 ]. Extension services and delivery techniques, on the other hand, are often unsuccessful in meeting the needs and technological hurdles that farmers face [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Agricultural extension and advisory services can help farmers address production and management issues by improving their technical knowledge, farm management skills, and information systems, resulting in increased production, higher economic returns, and a boost to the national and global economies [ 29 ]. Extension services and delivery techniques, on the other hand, are often unsuccessful in meeting the needs and technological hurdles that farmers face [ 29 ]. Moreover, farmers share their knowledge, bridging the gap between them and extension officers [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over time, governments of developed countries have reduced direct investments in agricultural extension (Laurent et al, 2006;Rivera, 2011). Moreover, in the developing world, agricultural extension has been described as "failing" (Government of Malawi, 2000), "moribund" (Eicher, 2001), "in disarray or barely functioning at all" (Rivera et al, 2001), or ineffective in responding to farmer demands and technological challenges (Ahikiriza et al, 2021). Factors like wealth, risk preferences, education, access and affordability of information and learning (Aker, 2011) can result in technology adoption slowing down and becoming more discontinuous, further threatening agricultural productivity (Oduniyi, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Smallholder dairy producers have tried several strategies to improve milk yielding, but these attempts involve several heuristics, time-consuming, and financial investments (Nyambo et al, 2019). Agricultural extension and consulting services are key players in farming growth, poverty mitigation, and food security (Ahikiriza et al, 2021). By advancing their technical knowledge, farm administration expertise, and information structure, farming extension and advice-giving facilities can assist farmers in identifying production and administration matters, which boosts productivity, higher returns on investment, and the growth of the national and global economies.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…For increasing milk, yielding dairy farmer groups should be aided in using technology to enhance quality and quantity production (Kyaruzi et al, 2019). Effective classification can help agricultural growth in SSA by informing extension services (Ahikiriza et al, 2021). It is reported that the predominance of these smallholders deprived their production perspective regarding commercialization and yielding (Nyambo et al, 2019).…”
mentioning
confidence: 99%